Welcoming and othering- civic immigrant education in Germany and the United Kingdom - Gorgen, KT (2020)
In a time when mass-migration across borders is both ubiquitous and heatedly debated, states in Europe turn to civics courses and citizenship tests to govern immigration and integration. Thus far, researchers have criticized civic immigrant education on normative grounds or have focused their investigations on individual countries. This in-depth study compares the content and structure of civic education for adult immigrants in Germany and the United Kingdom through the analytic coding of all official textbooks and test questions, 48 hours of observations in civics courses, and 41 interviews with immigrants and teachers. Operating within the theoretical framework of othering (Mead, 1934; Said, 1978), this research unpacks i) how national and immigrant identities are depicted in official civic immigrant education materials, ii) how immigrants respond to these identity depictions, and iii) what influence the structure of the education process has on immigrants’ civic learning in both countries.